Strength characteristic of reconstituted soils taken from Bacolor, Pampanga and Angeles, Pampanga - Torio, Lestelle V.; Zarco, Mark Albert H. (Quezon City College of Engineering, University of the Philippines Diliman, 2016)
Shear strength is essenti al for analyzing and solving limit ,state problems involving lateral earth pressures, bearing pressures and the slope stability. Many factors affect shear strength of soil including grain size, void ratio, mineralogy, saturation, and strain rate. This study investigates the factors affecting the strength properties of soils taken from Bacolor, Pampanga and Angeles, Pampanga using the direct shear test. Samples are tested to determine the response of the samples at varying conditions such as variation in void ratio, saturation and strain rate with the aim of determining the effects these factors have on the shear strength of the lahar samples. Soil properties obtained for samples from both sites are consistent with the properties of a redeposited lahar. Direct shear test results show that stress-strain plot or samples exhibit similar patterns as those of typical granular material. Samples from site 1 showed dilative behavior under dry and saturated conditions while samples from site 2 prepared with low relative density exhibited compressive behavior while denser samples exhibited volumetric change behavior characterized by compressive with weak dilation. Comparison of the shear strength obtained in the tests to previous studies also shows that the strengths obtained in the direct shear test are higher. The stiffness of the stress-strain response of the samples from both sites increased with increasing effective normal stress. Dilative behavior of samples under drained shear test from site 1 and site 2 tend to increase as relative density increases. Samples from site 1 exhibited dilative behavior for both dry and saturated conditions. Comparison of the stress-strain and volumetric change of samples sheared under 0.167%/min and 1.67%/min showed slightly higher calculated strength for samples from from both sites. Samples from site 1 sheared continuously showed decrease in strength under low and high relative density. On the other hand, samples from site 2 approached similar values for residual shear strength. Denser samples did not achieve peak strength when continuosly sheared. Sheared samples that are reconsolidated and resheared showed decrease in strength for samples taken from site 1. Sheared samples from site 2 also exhibited the same stress-strain behavior for relatively loose sample but do not achieve peak strength for denser sampel. Premature yielding is evident in most results obtained from the direct shear apparatus. This may be attributed to particle rearrangement and breakge during low strains. Reconstituted samples are used in performing the tests and values obtained in this study are only valid for reconstituted samples.
Thesis (M.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Shear strength of soils -- Testing; Soils -- Testing -- Philippines -- Pampanga; Lahars